2019
DOI: 10.1111/jace.16780
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation resistance of Ti3AlC2 and Ti3Al0.8Sn0.2C2 MAX phases: A comparison

Abstract: Ti3AlC2 and Ti3Al0.8Sn0.2C2 MAX phase powders are densified using Spark Plasma Sintering (SPS) technique to obtain dense bulk materials. Oxidation tests are then performed over the temperature range 800°C‐1000°C under synthetic air on the two different materials in order to compare their oxidation resistance. It is demonstrated that, in the case of the Ti3Al0.8Sn0.2C2 solid solution, the oxide layers consist in TiO2, Al2O3, and SnO2. The presence of Sn atoms in the A planes of the solid solution leads to an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…The high-oxidation resistance mechanism of Alcontaining MAX phases can be attributed to the fact that the weakly bonded Al elements diffuse to the surface at high temperatures and form a dense and continuous Al 2 O 3 layer on the surface, which effectively limits the inward diffusion of O À2 . [123,124] Several factors have significant influences on the oxidation behavior of MAX phases, including oxidation temperature, grain size, and solid-solution composition. Figure 15a,c shows the weight gain per unit surface area as a function of oxidation time for Ti 2 AlC.…”
Section: Oxidation Resistance Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…The high-oxidation resistance mechanism of Alcontaining MAX phases can be attributed to the fact that the weakly bonded Al elements diffuse to the surface at high temperatures and form a dense and continuous Al 2 O 3 layer on the surface, which effectively limits the inward diffusion of O À2 . [123,124] Several factors have significant influences on the oxidation behavior of MAX phases, including oxidation temperature, grain size, and solid-solution composition. Figure 15a,c shows the weight gain per unit surface area as a function of oxidation time for Ti 2 AlC.…”
Section: Oxidation Resistance Propertymentioning
confidence: 99%
“…Otherwise, a discontinuous Al 2 O 3 layer with TiO 2 layer on top is formed, and parabolic kinetics is observed, and the sample shows weaker oxidation resistance. [14,124] Figure 15e,f shows the cross-section view of the oxide layer observed by scanning electron microscopy (SEM) on Ti 3 AlC 2 samples after oxidation at 800 C for 24 and 500 h, [123] respectively. The thickness of the oxidized surface layer increased from %7 μm (24 h) to %200 μm (500 h).…”
Section: Oxidation Resistance Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, obtaining Ti 3 AlC 2 in a single-phase is quite difficult due to the narrow phase domain in the Ti-Al-C phase diagram [15]. The earlier studies revealed that secondary phases such as TiC, Ti x Al y , Al 2 O 3 , or the 211 MAX phase (Ti 2 AlC) are commonly detected in the end products [16][17][18]. In addition, there are two main problems for the large- * Correspondence: aysenurgencer@gmail.com scale production of highly pure Ti 3 AlC 2 powders.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Sn addition would solve the evaporative loss of Al and the thermal explosion simultaneously, and does not remain as impurities in the product of Ti 3 AlC 2 powders [5]. Moreover, the experimental studies have considered the Ti 3 Al 0.8 Sn 0.2 C 2 compound for the hardness [15], oxidation resistance [18], and compressive behavior [21] as well as with Ti 3 AlC 2 . However, there is a lack for the detailed properties of Sn doped Ti 3 AlC 2 in the literature.…”
Section: Introductionmentioning
confidence: 99%